2020
DOI: 10.1590/1678-9865202033e190164
|View full text |Cite
|
Sign up to set email alerts
|

Trends in food consumption of schoolchildren from 2nd to 5th grade: a panel data analysis

Abstract: Objective To identify trends in food consumption among schoolchildren (2nd-5th grades) from public schools in the city of Florianópolis, Brazil, in a period of three years. Methods Three cross-sectional surveys were carried out in 2013 (n=1,942), 2014 (n=1,989) and 2015 (n=2,418). Dietary intake data were obtained using the Web-Based Food Intake and Physical Activity of Schoolchildren questionnaire. Food items were aggregated to eight food groups. Kruskal-Wallis heterogeneity and trend tests were used to anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 30 publications
4
18
0
Order By: Relevance
“…The increase in the probability of belonging to the ‘Fruits and porridge’ SP may indicate an increase in fruit consumption, in line with the recommendation of the Brazilian Dietary Guidelines (Brazil, 2014) of consuming fruits, particularly as school snacks. Stratified analyses revealed that this increase occurred among younger children, similar to the findings of Pereira et al (2020). The authors investigated trends in the consumption of food groups, not dietary patterns, and identified a trend of increased intake of fruits and vegetables in children aged 7–9 years (Pereira et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The increase in the probability of belonging to the ‘Fruits and porridge’ SP may indicate an increase in fruit consumption, in line with the recommendation of the Brazilian Dietary Guidelines (Brazil, 2014) of consuming fruits, particularly as school snacks. Stratified analyses revealed that this increase occurred among younger children, similar to the findings of Pereira et al (2020). The authors investigated trends in the consumption of food groups, not dietary patterns, and identified a trend of increased intake of fruits and vegetables in children aged 7–9 years (Pereira et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…Stratified analyses revealed that this increase occurred among younger children, similar to the findings of Pereira et al (2020). The authors investigated trends in the consumption of food groups, not dietary patterns, and identified a trend of increased intake of fruits and vegetables in children aged 7-9 years (Pereira et al, 2020). However, a previous review reported that there is no consensus about the association of age and fruit consumption in children (Rasmussen et al, 2006).…”
Section: Discussionmentioning
confidence: 91%
“…The mean of the children's BHEI-R score was lower than that of their caregivers, indicating a greater need for dietary modification. Among the children, the girls obtained significantly higher scores than boys (p<0,05), similarly to findings of other studies [10,51]. Other studies using the BHEI-R have also demonstrated that a large percentage of individuals have a score that indicates the need for diet modification [36,23].…”
Section: Discussionsupporting
confidence: 87%
“…Obesity has a multifactorial character, among its main causes, and environmental factors stand out, such as socioeconomic conditions, lifestyle, and eating habits [2,[5][6][7][8][9]. Several instruments are used to assess food intake, which is one of the aspects of eating behavior [5,8,[10][11][12][13][14][15][16][17][18][19]. However, there is no foolproof assessment of the food consumption method [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, ‘Vegetables and leafy greens’ and ‘Fruits’ had the highest difficulty parameter, suggesting that compliance with the recommendation for fruit and vegetable consumption (≥three times/day) was the most difficult. Previous studies reported that schoolchildren have a low intake of fruits and vegetables [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%